A dedicated methodology for the development of new medical technologies - Isa C. T. Santos (2012)
The scientific discoveries of the last century are responsible for most of the medical devices currently in use. In this century, considering the advances namely in the computational power and the diffusion of the internet, one can expect a revolution in the use of medical technologies. Most certainly, new products and services will appear but only the ones that are supported by solid business plans will thrive. To assist in the development of novel medical devices and services and the elaboration of convincing business plans, the use of a product development methodology dedicated to medical technologies is suggested in this paper. Considering that many medical device companies spin-out from universities, this procedure aims to assist academia to cross the valley of death, i.e., the chasm between the world of research and the world of trade and industry.